A MATHEMATICAL MODEL OF DENGUE INTERNAL TRANSMISSION PROCESS - Nuraini, N.; Soewono, E.; Sidarto, K.A. (IndoMS, 2007)
In this paper we formulate a mathematical model of internal process of dengue virus transmission in the human body. We analyze the dynamic of dengue virus using a system of differential equation. We obtain a local stability of equilibrium for this model base on a threshold parameter. In particular, we prove the stability result for a free-virus and abundance of virus-states. Finally, numerical simulation of the model are performed to study the behaviour of the system for a short period of time.DOI :Â http://dx.doi.org/10.22342/jims.13.1.79.123-132